Spatial and temporal variability of snow cover in the southern forest-steppe of the Upper Ob River - N. I. Bykov; D. V. Chernykh; D. K. Pershin; R. Yu. Biryukov; L. F. Lubenets; D. V. Zolotov (Лëд и снег, 2022)
The study area is the forest-steppe in the Upper Ob basin located on the south of the West Siberian Plain. The results of studies of the dates of setting-up and loss of a stable snow cover and its duration are presented, the thickness of snow and snow storages for the period of maximum snow accumulation are analyzed. We used observational data obtained on routes and meteorological sites in 1966–2018 together with our own snow measurements of 2011–2019. It was found that in the southern forest-steppe, the duration of the stable snow cover presence decreases mainly as a result of its earlier destruction. At the same time, on the routes in a «ﬁeld» the thickness of snow and snow storage increase due to growth of winter precipitation. But no such trend is observed on the routes in a «forest» which is explained by inﬂuence of its canopy density. The snow cover here is unevenly distributed over the territory because the driﬅed snow transport depends mainly on features of the vegetation cover and the terrain relief. The route snow surveys performed near weather stations do not reﬂect the entire landscape diversity of the territory.